Economic Efficiency Of Optimizing The Market Of Transport Services Based On The Marketing LogisticsPrinciples - Irisbekova Mavluda Narinbaevna (Genius Journals, 2022)
This article is devoted to consideration of the methods aimed at improving current marketing of enterprises providing transport and logistics services, as well as creating a new efficient model of the structure and determining of net present value.
Keywords: Transport; classical; effectiveness; discounted income